Mutation and Characterization of an Albino Mutant of Monascus sp. Isolated from the Cikapundung River, Bandung - TIANA MILANDA; MARLIA SINGGIH WIBOWO; TUTUS GUSDINAR; HARYANTO DHANUTIRTO (Microbiology Indonesia, 2007)
Monascus sp. isolated from Cikapundung River, Bandung was mutated using ethyl methanesulfonate (2.5%, 90 min). Previously, this wild type was identified as Monascus purpureus ITBCC-HD-F001 employing random amplification polymorphic DNA (RAPD). Stability of the mutant was observed using color consistency and mutant stability (sub-culturing for five generations) tests. Genetic variation of the mutant (M. purpureus ITBCC-HDF002) was confirmed by RAPD. One of the DNA bands of 1150 bp was found in the albino mutant but not in the wild type, so it was considered as a genetic variation resulting from the mutation process. The albino mutant was characterized by comparing the growth curve, biomass production curve, and the monascidin A production curve of both strains i.e. wild type and the albino mutant. Monascidin A production of the mutant was higher than that of the wild type.